2010
DOI: 10.1186/1756-9966-29-153
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a new human pleomorphic malignant fibrous histiocytoma cell line, FU-MFH-2: molecular cytogenetic characterization by multicolor fluorescence in situ hybridization and comparative genomic hybridization

Abstract: BackgroundPleomorphic malignant fibrous histiocytoma (MFH) is one of the most frequent malignant soft tissue tumors in adults. Despite the considerable amount of research on MFH cell lines, their characterization at a molecular cytogenetic level has not been extensively analyzed.Methods and resultsWe established a new permanent human cell line, FU-MFH-2, from a metastatic pleomorphic MFH of a 72-year-old Japanese man, and applied multicolor fluorescence in situ hybridization (M-FISH), Urovysion™ FISH, and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…[1][2][3][4][5] Several recent studies, however, have described unique molecular and morphologic features, alongside behavioral features, of MFH that are not found in AFX or other tumor types. [6][7][8][9] The goal of this review is to analyze the current medical and scientific literature regarding MFH from the perspective of the practicing clinician in order to provide practical guidance regarding diagnosis and management of these tumors.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Several recent studies, however, have described unique molecular and morphologic features, alongside behavioral features, of MFH that are not found in AFX or other tumor types. [6][7][8][9] The goal of this review is to analyze the current medical and scientific literature regarding MFH from the perspective of the practicing clinician in order to provide practical guidance regarding diagnosis and management of these tumors.…”
Section: Introductionmentioning
confidence: 99%
“…27 More recently, a number of studies using comparative genomic hybridization have evaluated UPS and compared the findings to those of other pleomorphic sarcomas. [28][29][30][31] Interestingly, several studies have found striking similarities between UPS and pleomorphic leiomyosarcoma suggesting a shared lineage. 29,31 Clinical behavior…”
Section: Cytogenetic and Molecular Genetic Findingsmentioning
confidence: 99%
“…It would be preferable to compare UACC‐SARC1 to other RIS cell lines; unfortunately no other such lines are available to the scientific community. When comparing the RIS cell line UACC‐SARC1 to a metastatic MFH cell line that was not a RIS, both show numerous structural abnormalities on cytogenetic analysis . However, UACC‐SARC1 showed a relatively higher number of chromosomal losses versus gains.…”
Section: Discussionmentioning
confidence: 99%